Some characteristics of DNA and tropanoid pattern in Datura stramonium and Datura arborea - Tóvölgyi, Zsuzsa; Szabó, László Gy.; Stranczinger, Szilvia (JOURNAL OF LANDSCAPE ECOLOGY, 2005)
The investigations covered two species Datura stramonium and Datura arborea. In recent years paralell to increasing drug consumption in Hungary, besides using classical drugs alternative substances are becoming wide-spread. The latter category includes also Datura species, which are hallucinogens due to their alkaloide content. The amount of alkaloids was compared with thin layer chromatography in the two species. Recognising an atropine posoning is often difficult in routine medical practice. Molecular methods were used to determine and distinguish poisonings caused by Datura stramonium and D. arborea. The first step was DNA isolation from the samples then ITS4-ITS5 region was amplified. Afterwards sequence level differences were established with aligning sequences and finally enzymes were specified. The distinction was succesful both with chromatographic and molecular methods. The results serve as a basis for further studies.